Links between circulation indices and precipitation in the Mediterranean in an ensemble of regional climate models - Beranová, J.; Kyselý, J. (Jan) (Theoretical and Applied Climatology, 2016)
Spatial and temporal variability of precipitation in the Mediterranean is related to atmospheric circulation patterns such as the North Atlantic Oscillation (NAO), the Mediterranean Oscillation (MO) and the Western Mediterranean Oscillation (WeMO). This study examines ability of an ensemble of 12 regional climate model (RCM) simulations to reproduce observed links between these circulation indices and precipitation, as well as how these links may change in the late twenty-first century. We focus on the winter season and differences in precipitation amounts on the highest and lowest 25 % of days according to a given index. The relationships are evaluated against the E-OBS data set for 1961–1990. The observed pattern of differences in precipitation between positive and negative phases is generally similar for MO and NAO, which relates to the high correlation between these indices. Most regional climate models (RCMs) simulate links between the circulation indices and precipitation over most of the Mediterranean area reasonably well, especially for theMO andWeMO indices. The RCM with the largest deficiencies in reproducing the links is HadRM for all indices. The spatial patterns of differences in daily precipitation under positive and negative phases of the circulation indices for the future scenario (2070–2099) are similar to those for the control climate for all indices. This suggests that NAO, MO and WeMO are likely to play similar roles in affecting precipitation in the Mediterranean also in the future. However, increased NAO and decreased WeMO index, projected in most examined RCMs for the late twenty-first century in winter, may affect overall precipitation patterns.